PERBANDINGAN ANTARA HUKUM POSITIF DENGAN HUKUM ISLAM MENGENAI PEMBAGIAN HARTA BERSAMA AKIBAT PERCERAIAN - Masrokimin Masrokimin (Universitas Semarang, 2016)
Positive Law of the treasure together for this is still not the Resolute to provide rules on the division of the problem treasure together all still feel ambiguous are no rules that specify the split of the treasure together in KHI (Compilation of Islamic Law) by dividing equally that half to his wife and half for husband , but in a specific case by case if all decisions jointly owned by such disputes will be found, less able to reflect the sense of justice by a particular party, the Islamic law there is no clear division of the treasure together, both in classical and contemporary jurisprudence, is not even found in Al-Quran or Al-Hadith on this issue, there are certain differences in solving problems of common property, from differences in both the Positive Law and Islamic Law regarding subdivision and settlement when there is a dispute about the treasure joint will be obtainedcomparison, the ratio will be understood as a positive step in understanding and explore how the distribution and completion of this common treasure, so that would be obtained justice for those who want to resolving the problem treasure together.Legal dispute settlement joint property according to the Law-Marriage Law No. 1 of 1974 and the Compilation of Islamic Law that according to article 37, that is: